A time series analysis of transparent exopolymer particle distributions and C : N stoichiometry in the subtropical North Pacific: a key process in net community production and preformed nitrate anomalies? - K. Curran; T. A. Villareal; R. T. Letscher; R. T. Letscher (Biogeosciences)
Within the oligotrophic subtropical oceans, summertime dissolved inorganic carbon drawdown despite nutrient limitation in surface waters and subsurface oxygen consumption in the absence of Redfieldian stoichiometric nitrate release are two phenomena still awaiting a full mechanistic characterization. Many processes may contribute to these anomalies, including N2 fixation, non-Redfieldian DOM (dissolved organic matter) cycling, vertically migrating phytoplankton, heterotrophic NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="53e1f98be2cdf70dbe180d95894fc6b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3515-2025-ie00001.svg" width="9pt" height="16pt" src="bg-22-3515-2025-ie00001.png"/></svg:svg> uptake, and vertical-NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="0aaab3ee324d7a9ba8e4b96f67d8036e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3515-2025-ie00002.svg" width="9pt" height="16pt" src="bg-22-3515-2025-ie00002.png"/></svg:svg>-injection events. While these processes have been measured or modelled, they generally cannot fully account for the magnitudes of oxygen /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="57ee8123d9c9aefcf23d9c7f6463c158"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3515-2025-ie00003.svg" width="8pt" height="14pt" src="bg-22-3515-2025-ie00003.png"/></svg:svg> nitrate anomalies and the excess dissolved inorganic drawdown observed in many oligotrophic subtropical bodies of water. One other candidate process that may contribute to both phenomena is the formation of carbon-rich transparent exopolymer particles (TEPs) and Coomassie-stainable particles (CSPs) from dissolved organic precursors in surface waters and their subsequent export and remineralization below; however, few TEP and CSP data exist from the oligotrophic ocean. Here we present a multiyear time series (January 2020–September 2022) analysis of TEP, CSP, and total dissolved carbohydrate concentrations at station ALOHA (22°45′° N, 158° W) and along a meridional transect from 22°45′ to 31° N within the North Pacific subtropical gyre during June 2021. Exopolymer C : N stoichiometry at station ALOHA varied between 16.4 and 34.3, with values being more carbon rich in summer (26–34); ratios were higher (33–38) toward the gyre centre at 31° N. TEP concentrations were consistently elevated in surface waters through spring–autumn (4–8 µM C after carbon conversion) at station ALOHA, with lower concentrations (∼ 1.5–3 µM C) and a more uniform vertical distribution during winter, indicating that the TEPs that accumulate in surface waters may sink vertically and be exported with winter mixing. The accumulation of exopolymers in surface waters through spring–autumn and its subsequent vertical export may account for 6.5 %–20 % of net community production, helping to reduce the estimated imbalance of N supply and demand at this site to < 10 %. The upper-ocean exopolymer cycle may explain 22 %–67 % of the observed oxygen /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="165b352473919034209a9d51d0eaf41d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3515-2025-ie00004.svg" width="8pt" height="14pt" src="bg-22-3515-2025-ie00004.png"/></svg:svg> nitrate anomalies, helping to close the C, N, and O2 budgets at station ALOHA, while leaving room for significant contributions from other processes such as vertically migrating phytoplankton and heterotrophic nitrate uptake. These results suggest that exopolymer production and cycling may be more important to open-ocean carbon biogeochemistry and the biological pump than previously expected.